Performance characteristics of the VERSANT hepatitis C virus RNA 1.0 (kPCR) assay - Gruener, Nico; Viazov, S.; Korn, Klaus; Knöll, Antje; Trippler, M.; Schlaak, J. F.; Gerken, G.; Roggendorf, M.; Ross, R. Stefan (International Journal of Medical Microbiology, 2015)
HCV RNA assays are of central importance for virological diagnostics and for clinical planning and monitoring of an antiviral combination treatment of chronic HCV infections. The objective of the pre-market evaluation of the VERSANT HCV RNA 1.0 Assay (kPCR) was to collect analytical performance data for this new method of HCV RNA quantification and to compare them with the high standards that exist in this context. The assay exhibited a specificity of 100%. The mean intra- and inter-assay imprecision was 14.1% and 14.6%, respectively. The detection limit was determined to be 16IU/ml (95% confidence interval: 11.9-30.6IU/ml) and consequently corresponded to the manufacturer's claims (i.e. 15IU/ml). The test exhibited linearity for all HCV genotypes in a broad range from 15 to 10(8)IU HCV RNA/ml. Hence, the kPCR assay in general is well suitable for HCV RNA determinations in clinical practice. However, in a methodological comparison, a considerable under-quantification of the concentrations of HCV genotype 2 and 3 isolates was detected. Provided that the assay's manufacturer will quickly remedy this shortcoming, the VERSANT HCV RNA 1.0 (kPCR) can be called a completely reliable technique for HCV RNA quantification in routine virological diagnostics.
EVALuna2:8266